Ensuring equitable access, engagement and ability of socially and ethnically diverse participants to benefit from health promotion programmes: a qualitative study with parent carers of disabled children - Harniess, Phillip; McGlinchey, Caomhan; McDonald, Annabel; Boyle, Fleur; Garrood, Alice; Logan, Stuart; Morris, Christopher; Borek, Aleksandra J. (Frontiers in Public Health, 2024)
Background Equity is fundamental to health promotion programmes. However, unintentional or unseen barriers may exist for some underserved groups. We aimed to identify how to ensure equitable access and engagement for diverse parent carers of disabled children to benefit from health promotion programmes. Methods We purposively sampled parent carers with potentially intersecting characteristics including those who self-identified as from ethnic groups, whose children were educated other than at school, with sensory impairments, or neurodiversity, and fathers. Participants were recruited through local and national organisations and parent carer networks. Data collection involved semi-structured individual interviews, which were transcribed verbatim and analysed thematically and iteratively alongside data collection. Core researchers performed early analysis independently, followed by research team and advisory group cross-validation. Results Thirty-six parent carers with intersecting characteristics across the sampled backgrounds participated. We identified various perceived barriers around finding out about, attending and engaging with health programmes. We organised the findings into five themes focused on concepts capturing challenges and potential solutions to contextual barriers to access and participation in health programmes. (i) Reach – judiciously using targeted and universal strategies to ensure equitable distribution; (ii) Credibility – demonstrating trustworthiness of those advertising and/or delivering the programme; (iii) Opportunity – ensuring that the programme is seen as fulfilling a relevant need; (iv) Reservations – addressing barriers of readiness to participate; (v) Optimisation – tailoring to improve the inclusivity of the programme delivery. Conclusion We identified modifiable factors that impede members of some social groups from engaging with, and benefiting from, health promotion programmes, and potential solutions. We advocate a multifaceted approach is required from outreach to delivery, tailored to be mindful of extant diverse needs of parent carers in underserved communities. We catalogue key considerations to inform implementation strategies to optimise equity in health programmes for parent carers. The implications are likely transferable to other interventions and contexts. Key words: behaviour change interventions, health inequality, wellbeing, caregivers, implementation science, interviews